2004
DOI: 10.1038/sj.bjp.0705656
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic inhibition of spontaneous acetylcholine release induced by adenosine at the mouse neuromuscular junction

Abstract: 1 At the mouse neuromuscular junction, adenosine (AD) and the A 1 agonist 2-chloro-N 6 -cyclopentyl-adenosine (CCPA) induce presynaptic inhibition of spontaneous acetylcholine (ACh) release by activation of A 1 AD receptors through a mechanism that is still unknown. To evaluate whether the inhibition is mediated by modulation of the voltage-dependent calcium channels (VDCCs) associated with tonic secretion (L-and N-type VDCCs), we measured the miniature endplate potential (mepp) frequency in mouse diaphragm mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 60 publications
(86 reference statements)
6
26
2
Order By: Relevance
“…As we have observed in our previous papers (Cinalli et al, ; De Lorenzo et al, ; Guarracino et al, ; Palma et al, ; Veggetti et al, ), our experiments do not reveal any involvement of endogenous purines at basal conditions (K + 5 mM), since incubation of the diaphragms with the antagonists for the P2Y 13 , A 1 , A 3 , or A 2A receptors (AR‐C69931MX, DPCPX, MRS‐1191, or SCH‐58261, respectively) did not affect spontaneous neurotransmitter secretion. On the contrary, the application of exogenous agonists for P2Y 13 , A 1 , or A 3 receptors (2‐MeSADP, CCPA, or inosine, respectively) decreases MEPP frequency, whereas the A 2A receptor agonist CGS‐21680 increases it.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As we have observed in our previous papers (Cinalli et al, ; De Lorenzo et al, ; Guarracino et al, ; Palma et al, ; Veggetti et al, ), our experiments do not reveal any involvement of endogenous purines at basal conditions (K + 5 mM), since incubation of the diaphragms with the antagonists for the P2Y 13 , A 1 , A 3 , or A 2A receptors (AR‐C69931MX, DPCPX, MRS‐1191, or SCH‐58261, respectively) did not affect spontaneous neurotransmitter secretion. On the contrary, the application of exogenous agonists for P2Y 13 , A 1 , or A 3 receptors (2‐MeSADP, CCPA, or inosine, respectively) decreases MEPP frequency, whereas the A 2A receptor agonist CGS‐21680 increases it.…”
Section: Discussionsupporting
confidence: 81%
“…It was demonstrated that both purines, ATP and adenosine, modulate neurotransmitter release operating via presynaptic P2 and P1 receptors, respectively (De Lorenzo, Veggeti, Muchnik, & Losavio, ; Giniatullin & Sokolova, ; Sebastião & Ribeiro, ; Sokolova, Grishin, Shakirzyanova, Talantova, & Giniatullin, ). In previous reports performed in mouse neuromuscular junctions, we have found that at basal conditions (K + 5 mM), ATP and adenosine regulate ACh secretion by activating presynaptic P2Y receptors (De Lorenzo et al, ; Guarracino, Cinalli, Fernández, Roquel, & Losavio, ; Veggetti, Muchnik, & Losavio, ) and A 1 and A 2A receptors (De Lorenzo et al, ; Palma, Muchnik, & Losavio, ), respectively. Moreover, we have recently demonstrated, by pharmacological and immunohistochemical assays, that A 3 receptors are also present at the motor nerve terminals and that these receptors may be activated by adenosine and its metabolite inosine (Cinalli, Guarracino, Fernandez, Roquel, & Losavio, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, acting on A 1 and A 2A receptors at the vascular smooth muscle, adenosine may increase muscle blood flow and thus nutrient availability (Poucher, 1996;Ray et al, 2002). Besides, adenosine has presynaptic effects, either facilitating or inhibiting the release of acetylcholine from the motor nerve through A 1 (Correia-de-Sá et al, 1991;De Lorenzo et al, 2004) and A 2A (Correia-de-Sá et al, 2000;Baxter et al, 2005) receptors, respectively . Figure 10 summarizes the sequential steps of extracellular cAMP-adenosine pathway in the skeletal muscle, triggered by activation of cell-surface receptors coupled to G s protein, indicating the possible paracrine sites of adenosine action.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, direct glial activation would allow us to tease apart the underlying mechanisms, a task that would be difficult with endogenous activity alone since both the presynaptic terminal and PSCs bear many of the same types of receptors (e.g., A 1 and muscarinic ACh receptors) (Hamilton and Smith, 1991;Correia-de-Sá et al, 1996;Grafe et al, 1999;Galkin et al, 2001;Rochon et al, 2001;Oliveira et al, 2002Oliveira et al, , 2004De Lorenzo et al, 2004;Silinsky, 2004;Baxter et al, 2005;Moores et al, 2005;Todd and Robitaille, 2006;Dudel, 2007).…”
Section: Glial Calcium Elevations Are Sufficient To Induce Plasticitymentioning
confidence: 99%
“…Glial regulation occurs through a balanced A 1 /A 2A receptor activation Activation of A 1 and A 2A receptors results in inhibition and activation of different types of presynaptic calcium channels to regulate transmitter release at synapses in general and at the mammalian NMJ in particular (Correia-de-Sá et al, 1996;De Lorenzo et al, 2004;Oliveira et al, 2004;Silinsky, 2005;Cunha, 2008). Moreover, an adenosine-dependent long-term depression has been reported (Redman and Silinsky, 1994) that involves an inhibition of presynaptic calcium currents (Silinsky, 2004(Silinsky, , 2005.…”
Section: Glial Cells Decode Neuronal Signaling Through Calcium Dynamicsmentioning
confidence: 99%